A study of the relationship between maternal obesity and child under-nutrition in African women attending a child health clinic in Khayelitsha, Cape Town - Mvo, Ntombizodumo (Institute of Infectious Disease and Molecular Medicine, 2017)
Background: Malnutrition, manifesting as obesity in women and under-nutrition in children, is a major public health problem in South Africa. There is a multitude of epidemiological evidence reflecting the extent and health effects of these problems, specifically among the African communities. However, at a family level, there is a paucity of information regarding the relationship between obesity in mothers and under-nutrition in children. Studies set to explore this relationship and determinants of body size and nutrition from a cultural perspective are long overdue. Such studies would assist in identifying intervention strategies that are appropriate and effective for the population at risk. Objective: This study, therefore, investigated the relationship between the child's nutritional status and that of the mother in a peri-urban African community. It further explored knowledge, attitudes and perceptions of body size as possible determinants of obesity and under-nutrition. This will make information available for further screening and planning of culturally sensitive nutrition interventions for the population under study. Methods: The study was conducted in two phases. The first phase was an exploratory qualitative design used mainly to develop a questionnaire for the second phase. In-depth interviews were conducted with 10 obese African mothers, whose children were categorised on the 'Road-to-Health' card, as underweight. The interviews provided an understanding of the African women's' perceptions of their body sizes and nutrition regarding the child. The second phase utilised a cross-sectional analytic study design to investigate the relationship between the mother's weight and the child's weight. It further investigated the knowledge, attitudes and perceptions found in the first phase in a larger sample using appropriate statistical techniques. A systematic sample of 365 mother-child pairs attending a child health clinic over a two-month period, starting from August 1997, was selected. The sample included women between the ages of 16 and 49 years old and their children between the ages of 2 and 5 years old attending a child health clinic in Khayelitsha, a peri-urban area outside Cape Town. Anthropometric measurements of children and mothers were taken and a structured questionnaire was administered to the mothers. Findings: The qualitative study showed attitudes and perceptions of body size that were tolerant of a 'big' body image. There was a lack of knowledge regarding causes of obesity and effective ways of reducing weight, preventing chronic diseases of lifestyle and what constitutes 'good' nutrition for the child. All these findings were confirmed in the second phase of the study. The main study showed that less than half (42%) of the mothers were able to estimate their body weights. These mothers underestimated their weights, on average, by 5 kg (p=0.0001 CI: 3.5-6.8). In the total sample, 37.3% of the mothers were obese (BMI> 30kg/m2) and 33.4 % were overweight (25 <BMI < 30 kg/m 2). Sixty-eight (18.6%) children were stunted in terms of the NCHS reference values (z-score<-2 height-for-age), 13.2% underweight (z-score<-2 weight-forage) and 7.1 % were wasted (z-score<-2 weight-for-height). Only a small proportion (6.3%) were obese, z-score >2 weight-for-height. The main finding is that, overall, no relationship was found between the mother's weight and that of the child. The mother's BMI showed a weak positive correlation with the weight-for-age zscore. The relationship between BMI and height-for-age z-score or weight-for-height was not statistically significant. However, most importantly, subgroup analysis showed that mothers' perceptions of their own body size and that of the child were significantly related to BMI and weight-for-age z-scores. Furthermore, a higher proportion of obese mothers (47.1 %) were unhappy about their body size than non-obese mothers (35.4 %). Consequently, a lesser proportion of obese mothers (36%) chose an overweight body image as 'attractive' compared with non-obese mothers (40.2%). Conclusions: Although there was no relationship found between obesity in mothers and under-nutrition in children, this study confirmed the high prevalence of both problems in the study group. Furthermore, it provided new evidence on the relationship between nutritional status of mothers and the resultant attitudes and perceptions to body size. This crucial information could be used in planning appropriate intervention strategies for the study population. More studies of this nature are needed for specific target populations in order to direct effective interventions.